Facile Synthesis of Cellulose Acetate Nanofiber for Biosensing Application - Vasudevan, M. (Institute of Electrical and Electronics Engineers Inc., 2019)
Cellulose acetate (CA) is a renewable polymer resource which is used widely due to its unique characteristics which makes it to be a great candidate for various application. A novel approach on the synthesis of pure cellulose acetate (CA) and cellulose acetate/graphene (CA/G) nanofibers has been investigated. Field Emission Scanning Electron Microscopy (FESEM) characterization demonstrated the as-prepared CA nanofiber and CA/G nanofiber with nanofibrous structures. However, the nanofibers shows a major number of beads which categories the nanofibers as 'poor' quality fibers. Besides that, Fourier-transform infrared (FT-IR) analyses proves the presence of expected chemical bonding that assembled on the surfaces of the CA nanofibers. Hence, these nanofibers can be improved by carrying out more effective researches to obtain smooth and un-beaded nanofibers that can be utilized for future biosensing applications. Â© 2019 IEEE.